2021
DOI: 10.1038/s41467-021-27067-0
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature dynamic nuclear polarization enhanced NMR spectroscopy of small biological molecules in water

Abstract: Nuclear magnetic resonance (NMR) spectroscopy is a powerful and popular technique for probing the molecular structures, dynamics and chemical properties. However the conventional NMR spectroscopy is bottlenecked by its low sensitivity. Dynamic nuclear polarization (DNP) boosts NMR sensitivity by orders of magnitude and resolves this limitation. In liquid-state this revolutionizing technique has been restricted to a few specific non-biological model molecules in organic solvents. Here we show that the carbon po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Very recently, it has even been shown that significant DNPenhancement of up to 50-fold could be achieved for small biological molecules such as imidazole, amino acids, and glucose in aqueous solution at room temperature. 446 These strides may be complemented by efforts to move from cw μw irradiation toward pulsed DNP for coherent manipulation of electron and nuclear magnetization during transfer. This allows the excitation of peculiar DNP mechanisms such as NOVEL or TOP-DNP.…”
Section: Methodological Developments Of Dnp Toward Biomolecular Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, it has even been shown that significant DNPenhancement of up to 50-fold could be achieved for small biological molecules such as imidazole, amino acids, and glucose in aqueous solution at room temperature. 446 These strides may be complemented by efforts to move from cw μw irradiation toward pulsed DNP for coherent manipulation of electron and nuclear magnetization during transfer. This allows the excitation of peculiar DNP mechanisms such as NOVEL or TOP-DNP.…”
Section: Methodological Developments Of Dnp Toward Biomolecular Nmrmentioning
confidence: 99%
“…This currently requires the design of specialized probes which limit the samples extension into the electric field component of the μw field and provide efficient cooling of the miniscule solution volume. , Nevertheless, intriguing developments have been shown recently, such as the possibility to directly enhance the NMR signals of orientated lipids, promising the extendibility toward membrane proteins. Very recently, it has even been shown that significant DNP-enhancement of up to 50-fold could be achieved for small biological molecules such as imidazole, amino acids, and glucose in aqueous solution at room temperature …”
Section: Perspectives Developments and Outlookmentioning
confidence: 99%
“…However, the equipment is expensive because of the cryogenic temperatures required, and a continuous supply of polarized water is difficult. As a powerful room temperature DNP method, Overhauser DNP, which uses organic radicals, radical-triplet mixtures, or DNP using diamond defects are widely used. , However, the obtainable polarization is often limited to the difference in the gyromagnetic ratio (γ e /γ H ∼ 660), and the presence of paramagnetic species induces the spin–lattice relaxation of water and affects the resolution of NMR. Hyperpolarization with parahydrogen can also be applied to various molecules at room temperature, but the process is complicated because it requires chemical reactions and the isolation of products. , Therefore, although various hyperpolarization methods have been developed, providing continuously hyperpolarized water at room temperature is still a challenging and attractive mission.…”
Section: Introductionmentioning
confidence: 99%
“…The Overhauser effect (OE) DNP mechanism is the most promising approach for obtaining steady-state continuous hyperpolarization of nuclei in situ and at room temperature. Indeed, while the magnetic field dependence of OE is generally unfavorable, it has recently been shown that OE DNP can yield significant 13 C or 31 P signal enhancements at magnetic fields of ≤14 T. ,,, For example, Orlando et al have shown 13 C enhancements of ≤600 at 9.4 T for a 35 nL sample in a helix resonator . Dubroca et al also showed a 13 C enhancement of 70 and a 31 P enhancement of 160 with sample volumes of 100 μL at 14.1 T, using a custom solution NMR probe and microwave gating to minimize sample heating.…”
mentioning
confidence: 99%
“…In contrast, OE DNP to hyperpolarize 1 H in solution at high field is very inefficient . For example, Prisner and co-workers were able to hyperpolarize water with enhancements of −80 at 9.2 T, but only by using microwave superheated temperatures of 160 °C in an ∼1 nL sample volume; , recent improvements in probe design allowed sample volumes of ≤100 nL . There is thus great interest in hyperpolarizing 1 H nuclei in solution.…”
mentioning
confidence: 99%